The correct answer is x^2-2x+2=0
The explanation is shown below:
1. To solve the problem shown in the figure above, you must apply the following proccedure:
2. You have that the roots of the quadratic equation shown in the figure attached in the problem are:
x=-1±i
3. Then, you know the quadratic formula to solve quadratic equations, which is:
(-b±√(b^2-4ac))/2a
4. You can see in the figure that a=1 and c=2; then, by analizing this, you can conclude that the coefficient b is:
b=-2
5. Therefore, you can conclude tha the quadratic equation is:
x^2-2x+2=0
6. If you want to verify it, apply the quadratic formula to the quadratic equation shown above and you will obtain the roots shown in the figure.
•Using the formula the first term is a1 = −3
•Using the formula the second term is a2 = −1
•Using the formula the third term is a1 = 6
•Common difference formula:
a2 - a1 = (-1) - (-3) = 2
Answer:
The answer is x = 7
Step-by-step explanation:
3(x+2) - x + 8
Open the bracket
3(x + 2) distribute
3x + 6
3x + 6 - x + 8
combine the like terms
3x - x + 8 + 6
2x + 14
Please mark me as brainliest
F + 8 - 8 ≤ 3 - 8
f <span>≤ -5
next one
f + 9 - 9 </span><span>≥ -4 - 9
f </span><span>≥ -13 </span>
Answer:
1 2/5
Step-by-step explanation:
3/5 + 4/5= 7/5
7 - 5= 2
1 2/5